On (∈, ∈∨qk)-Fuzzy Hyperideals in Ordered LA-Semihypergroups. (8th July 2018) - Azhar, Muhammad; Yaqoob, Naveed; Gulistan, Muhammad; Khalaf, Mohammed M.
Abstract : The concept of( ∈, ∈ ∨ q k ) -fuzzy hyperideal of an ordered LA-semihypergroup is introduced by the ordered fuzzy points, and related properties are investigated. We study the relations between different( ∈, ∈ ∨ q k ) -fuzzy hyperideal of an ordered LA-semihypergroup. Furthermore, we study some results on homomorphisms of( ∈, ∈ ∨ q k ) -fuzzy hyperideals.